HGG-02. DIANHYDROGALACTITOL (VAL-083) OVERCOMES MGMT- AND P53-MEDIATED CHEMO-RESISTANCE AND DISPLAYS SYNERGY WITH TOPOISOMERASE INHIBITORS. (31st May 2017) - Zhai, Beibei; Steino, Anne; Bacha, Jeffrey; Brown, Dennis; Daugaard, Mads; Nicolaides, Theodore
Abstract: The mortality rate of pediatric CNS cancer has not decreased as other pediatric cancers, and high-grade gliomas (HGG) are the main cause of death in children with brain tumors. Children with HGG have few therapeutic options and 5-year survival is less than 20%. Relapsed HGG have a uniformly fatal outcome despite all available treatments. The standard treatment for HGG is surgery followed by radiotherapy and temozolomide (TMZ) although the efficacy of TMZ in children is negligible. DNA repair protein O6-Methyl-Guanine-DNA-MethylTransferase (MGMT) is expressed in most pediatric HGG and expression is correlated with resistance to TMZ and nitrosoureas and dismal prognosis. VAL-083 is a bi-functional alkylating agent that readily crosses the blood-brain barrier and has demonstrated activity in pediatric brain tumors as well as a favorable safety profile in prior NCI-sponsored clinical trials. VAL-083 induces interstrand cross-links at guanine-N7 causing DNA double-strand breaks and cancer cell death. VAL-083 overcomes TMZ-resistance and is equally active against GBM cancer stem cells (CSCs) and non-CSCs independent of MGMT status, in vitro. We recently showed that VAL-083 leads to irreversible S/G2-phase cell cycle arrest and persistent activation of the homologous recombination DNA repair pathway. This mechanism-of-action of VAL-083 suggests the potential for synergy with topoisomerase inhibitors (TOPi), commonly used in the treatment of pediatric HGG, which require cancer cells to be in S-phase for optimal efficacy. Here, VAL-083 cytotoxicity and DNA damage-response was evaluated in SF188, Med8a, A549 and PC3 cell-lines. We report strong activity in p53-mutated Med8a and SF188 cells known to be radio- and chemo-resistant. Further, we report synergy between VAL-083 and both topoisomerase I and II inhibitors (camptothecin and etoposide) in both A549 and PC3 cell-lines. Our results support a distinct anti-cancer mechanism for VAL-083 compared to standard HGG chemotherapy, resulting in the ability to overcome chemo-resistance and exhibiting synergy with TOPi.